Analysis Of The Effect Of Knowledge Sharing And Risk Management On Performance - Rahmat Hidayat; Fourtina Dewi; Revi Sesario; Yulia Novita; Lia Marthalia (Community Engagement and Emergence Journal (CEEJ), 2026)
This study aims to examine the role of knowledge sharing and risk management on performance in private companies. Using a quantitative research approach, data were collected from 100 employees through purposive sampling techniques. Data were analyzed using partial least squares (PLS) regression, assisted by SmartPLS version 3.29. The results showed that knowledge sharing does not a significant positive effect on employee performance, indicating that employees who practice knowledge sharing experience better performance and tend to be more engaged in their work. risk management does not have a significant impact on employee performance. these findings suggest that private companies that want to improve employee performance should not only rely on risk management factors, but should also focus on developing strong knowledge sharing that strengthens engagement at all levels of the organization